(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
Nefopam hydrochloride (NFH) is one of the centrally acting NSAIDs drug used for pain management. The main objective of this research is to study the effect of ratio of Cellulose acetate: Polyethylene glycol (PEG) 3350 and % weight gain in extended release (ER) coating of push-pull osmotic pump (PPOP) tablets, optimized by design of experiment (DoE) using response surface face center (α=1), central composite design having two independent variables at three levels. PPOP tablets of NFH was administer once in a day to reduce dosing frequency and improve patient compliance. PPOP tablets contains drug layer and push layer, compressed in to bilayer tablets which is further coated with cellulose acetate (CA) as semipermeable membrane polymer and PEG 3350 as a plasticizer or pore forming agent. ER coated tablets mechanically drill 0.50mm on drug layer part for the controlled release of drug up to 24 hrs. Based on the results it can be concluded that the ratio of CA: PEG 3350 and % weight gain in ER coating of PPOP tablets shows significant impact on % drug release. At lower % of PEG, burst release was observed due to cracking of ER coating layer, while at higher % of PEG, slightly rapid release of drug was observed. % Drug release is decrease with increase in the % weight gain of tablets. PPOP Tablets with 10% of PEG 3350 (Ratio of CA:PEG 3350, 90:10) and 8% weight gain exhibits zero order kinetic drug release up to 24 hrs.